Portable Systems for Metered Dispensing of Aggressive Liquids. (October 2018) - Volden, T.; Goldowsky, J.; Schmid, N.; Revol, V.
Precise metering in liquid dispensing applications often requires application-specific solutions due to incompatibilities of the sensor and actuator components with the dispensed liquids. Some reoccurring challenges are aggressive liquids that would damage the sensors or tubing, the need for sterile liquids while the pumps or sensors cannot be sterilized, or media that can clog the sensor channels. Two different dispensing systems are here presented where the dispensing flow rate or volume is indirectly measured through a coupled pressure change or airflow, thus avoiding contact between the sensor and liquid. The controlled pressure-driven dispensing (cPDD) system builds an overpressure in the liquid reservoir by pumping air and controls the opening of the liquid output valve based on the internal pressure development. The FlowCap system uses a liquid pump on the outlet, controlled by the measured inflow of air to the reservoir. Both systems are designed for compactness and portability and offer independent operation, as well as control and communication, over a wireless interface.